SHOCKWAVES RESULTING FROM HIGH PRESSURE DIESEL FUEL INJECTION CFD & EXPERIMENTAL GRAPHICAL RESULTS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
Recent experimental research has shown that when injecting diesel fuel at 5000 bar in a combustion chamber at 300 °K, shockwaves are induced. Such shockwaves have demonstrated their influence on improving combustion, however the mechanism behind this improvement isn’t fully understood. This paper takes recently published experimental work another step, using a CFD numerical solution. Graphical results and fluid mechanics theory was then used to explain the impact of such shockwaves on the liquid fuel’s droplets thermo fluid effects. Methodology involves building a CFD model capable of handling supersonic and subsonic fluid flows, and then generate graphic results. Graphical CFD results were validated against graphical experimental results, with regards to the presence of shockwaves. Confirming the induction of shockwaves in recent experimental research. It was concluded that shockwaves can influence fuel droplet evaporation rate by influencing; (a) the Nusselt and Prandtl numbers, as shown in Eq. (1) to (4), and subsequently (b) influencing the evaporation of a liquid fuel droplet as in equation (8). Shockwaves are energy carriers and therefor a fuel droplet can be influenced as it is crossed by the shockwave. High pressure fuel injection inducing shockwaves improves air/fuel combustion and not just what is traditional thought (finer droplets & turbulences).